Strengthening EduTech Company Performance Through Knowledge Practices and Organizational Learning - Evasari, Cantika Putri; Arif, Moh. Erfan (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – Educational Technology (EduTech) industry in Indonesia rapidly grows along the digital transformations in education sector. However, fierce competitions and highly dynamic markets prompt edutech companies to consistently enhance their internal capability and organizational performance. The objective of this research is to analyze the effects of knowledge management practices, organizational learning, and knowledge sharing on the performance of PT Pintar Pemenang Asia.   Design/methodology/approach – Using saturated or census sampling, all 80 members of the population employees of the edutech company were selected as the sample of this quantitative explanatory study. The data was harvested via a questionnaire survey and was analyzed through multiple linear regression in IBM SPSS 25. Findings – The results show that knowledge management practices, organizational learning, and knowledge sharing significantly influence the company performance. Originality/value – This study offers a novel integrative model that simultaneously examines the effects of knowledge management practices, organizational learning, and knowledge sharing on company performance within the Indonesian educational technology (EduTech) sector. Unlike prior research, it highlights the specific context of an EduTech firm involved in the government’s Prakerja program, addressing unique operational and policy challenges. The findings enrich the literature by confirming the theoretical linkage between knowledge-based resources and firm performance while providing practical insights for developing sustainable knowledge strategies in technology-driven industries.